2018
DOI: 10.1080/2162402x.2018.1515057
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEK with trametinib enhances the efficacy of anti-PD-L1 inhibitor by regulating anti-tumor immunity in head and neck squamous cell carcinoma

Abstract: Major histocompatibility complex (MHC) class I downregulation is the primary immune evasion mechanism associated with failure in anti-PD-1/PD-L1 blockade therapies for cancer. Here, we examined the role of MEK signaling pathway inhibition in head and neck squamous cell carcinoma (HNSCC) both in vitro and in vivo. We found that trametinib, a small molecule inhibitor of MEK, significantly enhanced MHC class I and PD-L1 expression in human HNSCC cell lines, and this occurred via STAT3 activation. Trametinib also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 44 publications
5
51
0
Order By: Relevance
“…Blocking the interaction using anti-PD-1 antibody prevents negative signaling and enhances the anti-tumor T cell response. A recent study has shown that anti-PD-L1 antibody therapy failed to inhibit SCC VII tumor growth, but combination treatment with MEK inhibitor and anti-PD-L1 antibody showed a synergistic effect in inhibiting tumor growth [35]. Our study demonstrates that early administration of anti-PD-1 antibody treatment inhibits SCC VII tumor growth and induces a durable protective anti-tumor immunity, suggesting that SCC VII cells are immunogenic.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Blocking the interaction using anti-PD-1 antibody prevents negative signaling and enhances the anti-tumor T cell response. A recent study has shown that anti-PD-L1 antibody therapy failed to inhibit SCC VII tumor growth, but combination treatment with MEK inhibitor and anti-PD-L1 antibody showed a synergistic effect in inhibiting tumor growth [35]. Our study demonstrates that early administration of anti-PD-1 antibody treatment inhibits SCC VII tumor growth and induces a durable protective anti-tumor immunity, suggesting that SCC VII cells are immunogenic.…”
Section: Discussionsupporting
confidence: 52%
“…The SCC VII squamous cell carcinoma cell line is derived from the abdominal cavity of C3H mice [50][51][52], but widely used as a model for squamous cell carcinomas of head and neck cancer as it behaves similarly to human HNSCC [28,29,35,53]. In this study, we compared the efficacy of the TMV vaccine immunotherapy in SCC VII with recently available MOC models [7,31,33,37].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced MEK activity can cause abnormal activation in the RAS-RAF-MEK-ERK pathway, which has been reported to be responsible for the pathogenesis of inflammation and approximately 30% of all human malignancies [4,5]. Thus, MEK has been the target of various drug discoveries [6][7][8][9][10][11][12][13][14], and inhibition of MEK activity may be used to treat MEK pathway activation-driven cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, for example, we show that apigenin suppressed the TNFα mediated rise in a potent tumor suppressor: CXCL10. While previous studies consistently that CXCL10 is up-regulated in normal vs. tumor tissue (76,77) this particular protein acts as the major tumor suppressor, evoked by IFN-γ treatment and somehow plays a role in the re-expression of MHC-1, PD-L1, the infiltration of anti-tumoral CD4(+) and CD8(+) T cells (78,79), NK cells, cytotoxic lymphocytes (CTLs) to the tumor to turn on immune surveillance and heighted survival odds in diverse human cancers (80)(81)(82). While the beneficial effects of apigenin in cancer are consistently reported, any compound that would turn off the CXCL9, -10, -11/CXCR3 axis could harm the host immunes system to destroy self-malignant tumor tissue (83).…”
Section: Discussionmentioning
confidence: 99%